Espace urbain et échanges chez les Ye’kuana à Boa Vista, Roraima (Amazonie brésilienne) - Elaine Moreira (Développement Durable et Territoires)
This article explores the Ye’kuana’s social dynamics between their villages in Brazil and Roraima’s State Capital, Boa Vista. The circulation of people and their building of contacts’ networks are analysed as related to their entry strategies into new labour markets linked to education and health public policies for indigenous peoples in Brazil. Their return to home villages with a paid job, as well as the circulation of food products between villages and town, are also analysed in this context, where family cares between relatives remain present, as needed.